(untitled) (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT : This research aims to know the role of the Regional Electoral Commission in organizing the election head East halmahera Regency area. And to know how the electoral region of East Halmahera Regency in increasing participation in the election of the head of the region. Electoral Commission is chosen and defined by law the inaugural election, where at the beginning of its formation, the Electoral Commission is the agency that consists of people who are nonpartisan and most of the colleges and non-governmental people. The regional Election Commission is subordinate to the Central Electoral Commission to organize the elections are tiered. The research methods used in this research is qualitative, descriptive methods, using primary data collection techniques. While the primary informants amounted to 3 people, yaitu: 1. Technical Defisi technical election subsection coconut and public relations Head of Sub-Division 3 programs and data and additional informants, those who can provide information although not directly involved in social interaction that is thorough, people namely , academic, and religious figures. From the results of the examination can be conclude that the performance of the Regional Electoral Commission East Halmahera in increasing community participation in elections of the head of the area can already say good, because in this case there is the occurrence of an increasing number of voters being 70%, in addition also many promotional activities and socialization activities performed by the Regional Electoral Commission in order to attract sympathetic community. Reference from the conclusions above, in order that the Commission recommend to the regional elections of East Halmahera can be more enterprising again socialisation in order public participation in choosing the higher. Key words: Regional Electoral Commission and community participation